Effect of Electrohydrodynamic (EHD) on the Drying Rate of Polymer Films Based on the Heat and Mass Transfer - N. Mirhoseini renani; N. Etesami (Iranian Journal of Chemical Engineering)
The electrohydrodynamic (EHD) drying of Poly (vinyl acetate) latex films was experimentally investigated in a wind tunnel. The influence of various conditions such as the air temperature, air velocity, and concentration of the latex solution, in the presence and the absence of a high electric field, was investigated. The effects of the applied voltage intensity, electrode gap, number of needle electrodes, and polarity of corona on the drying rate of polymer films were studies. The drying behavior of films in a wind tunnel was observed by the weighting method and analyzed based on the heat and mass transfer. Results showed the importance of the EHD role in the drying rate of the polymer film. Increasing the intensity of the electric field, number, and configuration of needle electrodes, and decreasing the electrode gap lead to a significant enhancement of the drying rate of the polymer film. Scanning electron microscope (SEM) images were used to analyze the effect of EHD on the morphology of dried films.